The Relationship between Agility and Dribbling Futsal Skills at State High School 04 Bengkulu Selatan - Pendri Kurniawan Putra (Penerbit Jurnal Indonesia, 2021)
The ability to dribble in each athlete varies greatly, there are similarities and differences. These similarities and differences can be seen from the mastery of dribbling techniques, both from speed when dribbling and from agility when dribbling. The results of these observations raise a problem, namely whether dribbling is affected by agility? The author formulates the problem, namely how is the relationship between agility and futsal ball dribbling ability? This study aims to determine whether there is a relationship between agility and dribbling ability. To solve this problem, the writer uses a descriptive method with a correlational study. The population used was all futsal athletes at SMA Negeri 04 Bengkulu Selatan, the sample was taken as many as 22 athletes. The instrument used in this research is agility measurement. The results showed that the value of rcount with rtable at = 5% with n=22 obtained an rtable of 0.423. Because the correlation coefficient between rx.y = 0.61 > r(0.5)(12) = 0.423, it means that there is a significant relationship between agility and dribbling skills of Futsal athletes at SMA Negeri 04 Bengkulu Selatan.